Effect of bio-fertilizers Application and Nutrient Solution Calibor Spray on growth of Pomegranate cv. Wonderful Seedling - Al - Hayani, Ali Mohammed; Suhail, Faris Mohammed; Kamel, Salam Khaled (Journal of agricultural, environmental and veterinary sciences, 2018)
The experiment was carried out in a fields belonged to the Department of Horticulture and Landscape Gardening / College of Agriculture - University of Diyala for the period 24- 2- 2016 to 1- 6- 2017 on wonderful pomegranate seedlings in order to know the effect of the treatment with a mixture of bio- fertilizers and spray with the nutritional solution(Calibour) on the vegetative traits of pomegranate seedlings var. Wonderful. Two- year- old pomegranate seedlings of equal size as much as possible were used and bacteriophages containing Azospirillum brasilense and Pseudomonas flourescence were added to the growth medium allocated to each seedlings at concentrations of 0، 10 and 20 g. Plants - 1 on 24/2/2016. Seedlings were sprayed with four levels of nutritious solution (0، 3. 5، 5، and 7 ml- 1. The experiment was carried out using Completely randomized Block Design(RCBD). The results can be summarized as follows: • The addition of bio- fertilizer significantly increased all vegetable growth parameters compared with untreated control. The third level of fertilizer gave the highest values ​​for the average increase in the diameter of the main stem and it’s length and the relative content of chlorophyll in leaves at both growth seasons. Spraying with nutrient solution Calibour significantly increased all vegetative growth parameters on both growth seasons. The second and third concentration of the solution did not differ significantly in all vegetative traits on both growth seasons (excluding the stem diameter in the second season). The positive effect on the traits was increased with overlap between the biofertilizers and nutrient solution treatments. The overlap between the second and the third concentration of nutrient solution with with the third level of biofertilizer gave the highest increase in all vegetative characteristics compared with untreated control(B0A0). • The addition of bio- fertilizer at all levels has resulted in a significant increase in the concentration of nitrogen and phosphorus in the leaves in both growth seasons compared to untreated control treatment. Spraying with the second and third concentration of the nutritious solution resulted in a significant increase in the NP nutrients concentrations in the leaves at both growth seasons compared with untreated control treatment. The interaction between the third level of biofertilizers، the second concentration of the nutritious solution and the second level of the biofertilizers with the third concentration of the nutrient solution significantly differed in the concentration of nitrogen in the leaves of the first and second growth seasons، respectively، compared with the lowest ratio in untreated control treatment. The third level of bio fertilizer and the third concentration of the nutritious solution showed the highest percentage of phosphorus concentration in leaves at both growth seasons compared to the lowest- percentage of untreated control treatment.